(untitled) (Bangladesh Journal of Medicine, 2023)
Background: Subclinical left ventricular dysfunction in type 2 diabetes mellitus (DM) patients may precede the development of symptomatic heart failure. Detecting this dysfunction early could potentially prevent its progression. However, there is a scarcity of studies on this topic in Bangladesh. Therefore, this study aimed to explore the left ventricular function status in type 2 DM patients without any known co-morbid conditions in a tertiary care hospital. Methods: A cross-sectional study was conducted at the Department of Internal Medicine in Sir Salimullah Medical College & Mitford Hospital over a one-year period. A total of 100 patients with a diagnosis of type 2 DM, meeting the inclusion-exclusion criteria, were enrolled. Written informed consent was obtained from each participant, followed by the collection of socio-demographic data, detailed clinical history, and routine investigations. Echocardiograms were performed on all participants to assess the presence of systolic and diastolic dysfunction using various modes. Data analysis was conducted using the statistical software SPSS 23.0. Results: The mean age of the study patients was 47.23±9.13 (SD) years, with the majority in the age group of 40-49 years (43%). Female patients accounted for 58% of the sample, while male patients comprised 42%. The frequency of left ventricular diastolic dysfunction (LVDD) was 65%. The presence of LVDD was associated with longer duration of diabetes mellitus, higher HbA1C levels, older age, and increased BMI (p<.05). Conclusion: The majority of type 2 diabetic patients in this study exhibited left ventricular diastolic dysfunction, with a prevalence of 65%. Further larger-scale studies are recommended to validate these findings. Bangladesh J Medicine 2023; 34(3): 229-234